NETWORK ANALYSIS OF PORTUGUESE TEAM ON FIFA WORLD CUP 2014 - Rui Sousa Mendes; Filipe Manuel Clemente; Fernando Manuel Lourenço Martins (Federación Extremeña de Balonmano; University of Extremadura, 2015)
Match analysis has been using in football case to identify properties and patterns of teams (Sarmento et al., 2014). From the regular notational analysis until the most recent computational tactical metrics, a lot of different outcomes can be possible to extract from a single match (Clemente, Couceiro, Martins, & Mendes, 2015). In the specific case of football, the cooperation among team-members is one of the main factors that contribute for a better performance (Grund, 2012). Thus, to analyse such cooperation the Social Network Analysis have been used to identify how team-members are connected and if there are cooperation tendencies inside the team (Clemente et al., 2015). The prominent players have been also analysed in order to identify the central players in the team (Clemente, Couceiro, Martins, & Mendes, 2014). Objectives: Therefore, using the social network analysis approach the aim of this study was to analyse the centrality levels of Portuguese positional roles during the FIFA World Cup 2014 and to identify the prominent tactical positions that determined the moments with ball.